2013
DOI: 10.1126/science.1239794
|View full text |Cite
|
Sign up to set email alerts
|

Paleofluvial Mega-Canyon Beneath the Central Greenland Ice Sheet

Abstract: Subglacial topography plays an important role in modulating the distribution and flow of basal water. Where topography predates ice sheet inception, it can also reveal insights into former tectonic and geomorphological processes. Although such associations are known in Antarctica, little consideration has been given to them in Greenland, partly because much of the ice sheet bed is thought to be relatively flat and smooth. Here, we present evidence from ice-penetrating radar data for a 750-km-long subglacial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 25 publications
(11 reference statements)
5
81
0
Order By: Relevance
“…For example, studies have found that in Northern Greenland changes in the subglacial waterways are likely to have taken place during the last glacial maximum (cf. Bamber et al, 2013b). The method outlined in this paper could be used to investigate the change in subglacial drainage patterns as the ice sheet retreated and thinned after the last glacial maximum to its present-day state.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have found that in Northern Greenland changes in the subglacial waterways are likely to have taken place during the last glacial maximum (cf. Bamber et al, 2013b). The method outlined in this paper could be used to investigate the change in subglacial drainage patterns as the ice sheet retreated and thinned after the last glacial maximum to its present-day state.…”
Section: Discussionmentioning
confidence: 99%
“…Henriksen, 2008) and larger-scale landscape features including subglacial drainage networks (Cooper et al, 2016;Chu et al, 2016;Livingstone et al, 2017) and palaeofluvial canyons (such the "mega canyon" feature observed in Fig. 6e, which has Petermann glacier as its modern-day terminus) (Bamber et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…We used high-resolution surface and subglacial topography, which exert primary control on the subglacial distribution and flow of water 5,63 . The geometry is prescribed using a 2008 SPOT surface digital elevation model (DEM) at 40-m resolution 64 , and a 500-m bed DEM produced from ice surface and thickness measurements from NASA's Operation IceBridge supplemented by additional radio-echo sounding data acquired by ground-based field campaigns.…”
Section: Methodsmentioning
confidence: 99%